Gastrointestinal tract carcinoid with carcinoid syndrome in 63-year-old diver - a case report - Hanna Dominik; Wojciech Pawęska; Barbara Dominik (Kazimierz Wielki University, 2023)
Introduction: Carcinoid is a tumor that originates from neuroendocrine cells.[1] It was primarily named and described in 1907 by Siegfried Oberndorfer to characterize neoplasms located in GIST with a relatively indolent course.[2] Term "carcinoid" is now used to describe. neuroendocrine neoplasms, a subset of rare tumors, mostly sporadic, which are typically located in gastrointestinal tract but they may also appear beyond it (e.g. in thymus or lungs).[2,3] NET's are highly differentiated and usually hormonally active. Biochemical proof of their presence can consist of a measurement of the released substances - serotonin, bradykinin, histamine, etc. [3]Carcinoid tumors derive from serotonin-producing enterochromaffin cells.[1] They contain high quantities of tryptophane that is transformed later into serotonin. This biogenic amine is responsible for occurrence of so called- carcinoid syndrome. It manifests with hot flushes, diarrhea, tachycardia, vertigo and excessive sweating.[3] The attacks usually last from 0,5 minutes up to half an hour and they can be triggered by food or alcohol consumption, liver palpation or general anesthesia. Due to excessive serotonin production, long lasting carcinoid might lead to right endocardial fibrosis with tricuspid valve and pulmonary valve dysfunction. [4] Description of the case: The following case describes the clinical history, diagnostic process, imaging studies and treatment applied to 63-year-old male professional diver who was admitted to University Hospital of Zielona Góra with a clinical picture that resembled carcinoid syndrome. The final diagnosis- carcinoid originating from the ileum- was settled after performing multiple studies. The patient was referred to the department of Endocrinology and Neuroendocrine Tumors in Silesian University Center in Katowice. He initiated therapy with Somatuline Autogel. The Tumor Board was conducted in order to determine the optimal treatment for the patient.